Redesain Lingkungan Kerja dengan Pendekatan Mikroklimatik Ergonomi untuk Menurunkan Kelelahan Kerja dan Meningkatkan Output Produksi di Masa Pandemic Covid 19 - Sajiyo, Sajiyo; Abdulrahim, Muslimin; Tasya Febrinda Ardika Putri; Sharhani Qisthinaningtyas (Journal of Research and Technology, 2022)
Fatigue is a system of protection against physical damage due to excessive activity, but is sometimes considered a negative factor, which affects work efficiency. Fatigue has an impact on performance. If the level of fatigue is high, it will cause a decrease in productivity, so that the production output target is not achieved. Work productivity is influenced by ergonomic working conditions. An ergonomic work environment is indicated by microclimatic conditions that comply with ergonomic standards. To create an ergonomic work environment, it is necessary to pay attention to microclimate which include: air temperature, air humidity, air circulation, and lighting (light intensity). For this reason, it is necessary to conduct research on "Redesigning the Work Environment with a Microclimate Ergonomics Approach to Reduce Work Fatigue and Increase Production Output During the Covid-19 Pandemic Period. The results of this study are the comparison of the results of microclimate measurements, measurements of worker conditions, measurement of the impact on the workspace in the old and new workspaces. So that the results of this study can help cigarette entrepreneurs, especially the home industry (home industry) in an effort to reduce work fatigue, and increase production output.